Targeting the Mitochondria-Proteostasis Axis to Delay Aging - Zimmermann, Andreas; Madreiter-Sokolowski, Corina; Stryeck, Sarah; Abdellatif, Mahmoud (Frontiers in Cell and Developmental Biology, 2021)
Human life expectancy continues to grow globally, and so does the prevalence of age-related chronic diseases, causing a huge medical and economic burden on society. Effective therapeutic options for these disorders are scarce, and even if available, are typically limited to a single comorbidity in a multifaceted dysfunction that inevitably affects all organ systems. Thus, novel therapies that target fundamental processes of aging itself are desperately needed. In this article, we summarize current strategies that successfully delay aging and related diseases by targeting mitochondria and protein homeostasis. In particular, we focus on autophagy, as a fundamental proteostatic process that is intimately linked to mitochondrial quality control. We present genetic and pharmacological interventions that effectively extend health- and life-span by acting on specific mitochondrial and pro-autophagic molecular targets. In the end, we delve into the crosstalk between autophagy and mitochondria, in what we refer to as the mitochondria-proteostasis axis, and explore the prospect of targeting this crosstalk to harness maximal therapeutic potential of anti-aging interventions.